VD_FINDINFO Jug / 2022 / 464 vom 2. Juni 2022 - VD Tribunal cantonal (2022)
DROIT ÉTRANGER, AUTORISATION DE TRAVAIL, EMPLOYEUR, DOL ÉVENTUEL, INTENTION, CONSTATATION DES FAITS | 12 CP, 10 CPP (CH), 117 al. 1 LEI